Construction of Electrochemical Immunosensing Interface for Multiple Cancer Biomarkers Detection. Issue 8 (3rd May 2016) - Wang, Liyuan; Rong, Qinfeng; Ma, Zhanfang
Abstract: The quick and early detection of cancer biomarkers is crucial for improving resectability rate and reducing mortality rate of cancer treatment. Cancer biomarkers detection with electrochemical assay has attracted considerable attention due to its high sensitivity, rapid response, high efficiency and good specificity. Recent developments of electrochemical immunosensing interface have significantly improved the sensitivity and efficiency by constructing substrates and immunoprobes using hybrid nanomaterials. As is known, electrochemical signal overlapping and sensitivity enhancement are two main challenges in the development of multiplexed electrochemical immunoassay. Many researches have been conducted to solve these problems and have received great progress. Herein, this review describes the recent advances of nanomaterials on the development of the electrochemical immunosensing interface for the detection of multiple cancer biomarkers and provides a perspective in this field. Abstract :